The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1111/j.1476-5381.1981.tb10477.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Catecholamine Release and Sodium Pump Inhibition in the Perfused Adrenal Gland of the Cat

Abstract: (10-4 M) inhibited the uptake of 86Rb into adreno-medullary tissue by 60%. Maximal inhibition had already occurred 2 min after adding the drug, indicating a lack of temporal correlation between ATPase inhibition and the ouabain secretory response, which took longer (about 30-40 min) to reach its peak. NEM (10-4 M) blocked 86Rb uptake in a similar manner. 6 The results are further evidence in favour of the presence of a Na+-Ca2+ exchange system in the chromaffin cell membrane, probably involved in the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
(26 reference statements)
3
18
0
Order By: Relevance
“…If Bay K 8644 were acting intracellularly in a step beyond the Ca channel, then secretory responses such as those induced by A23187 or activation ofthe Na/Ca exchange mechanism by Kfree solution, ought also to be potentiated by the dihydropyridine. Like ouabain, K deprivation inhibits the membrane Na+,K+-ATPase activity (Skou, 1957) causing the secondary activation by intracellularly accumulated Na, of a membrane Na/Ca exchange carrier that leads to an increased rate of catecholamine release (Garcia et al, 1981b). The experiment demonstrating that Bay K 8644 was unable to affect the profile of the secretory curve obtained with K-free solutions, strongly suggests that this drug is not acting on the Na/Ca exchange system of the chromaffin cell membrane to modify its activity.…”
Section: Discussionmentioning
confidence: 99%
“…If Bay K 8644 were acting intracellularly in a step beyond the Ca channel, then secretory responses such as those induced by A23187 or activation ofthe Na/Ca exchange mechanism by Kfree solution, ought also to be potentiated by the dihydropyridine. Like ouabain, K deprivation inhibits the membrane Na+,K+-ATPase activity (Skou, 1957) causing the secondary activation by intracellularly accumulated Na, of a membrane Na/Ca exchange carrier that leads to an increased rate of catecholamine release (Garcia et al, 1981b). The experiment demonstrating that Bay K 8644 was unable to affect the profile of the secretory curve obtained with K-free solutions, strongly suggests that this drug is not acting on the Na/Ca exchange system of the chromaffin cell membrane to modify its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of 45Ca efflux from the medullary slices (RINK, 1977) and the perfused cortex-free medulla (AGUIRRE et a!., 1977) was largely dependent on external Na. Conversely, all the procedures leading to a rise in the concentration of internal Na was found to increase Ca influx in exchange for internal Na (that is, Na-dependent Ca influx) thereby increasing catecholamine (CA) secretion (ESQUERRO et al, 1980;GARCIA et al, 1980GARCIA et al, , 1981bNISHIMURA et al, 1981;SORIMACHI et al, 1981;SORIMACHI and YAMAGAMI, 1983). Recently, GARCIA et al (1981a) reported that ouabain treatment of the adrenal gland enabled a small increment of external K to increase markedly the rate of CA secretion.…”
mentioning
confidence: 99%
“…In bovine chromaffin cells NCX1 can favour Na + -dependent Ca 2+ influx [143] or Ca 2+ export [144] and has been proposed to participate in the regulation of [Ca 2+ ] c and exocytosis in cat [150,161,162] and bovine chromaffin cells [142,143,153,[163][164][165]. In addition, chromaffin cells co-express NCX and the retinal rod-type K + -dependent Na + /Ca 2+ exchanger [166].…”
Section: Calcium Effluxmentioning
confidence: 99%